A randomized controlled trial of social skills training for patients with treatment-resistant schizophrenia with predominantly negative symptoms. (May 2020) - Kayo, Monica; Scemes, Silvia; Savoia, Mariangela Gentil; Bichuette, Alice; Abreu, Ana Claudia; da Silva, Emily Pereira; Baria, Patricia; Piovaccari, Victoria; Petreche, Beatriz; Bressan, Rodrigo Affonseca; Gadelha, Ary; Elkis, Helio
Highlights: This randomized trial evaluated the efficacy of social skills training (SST) in improving negative symptoms in patients with treatment-resistant schizophrenia in comparison with a control group. The patients were all taking clozapine and had predominantly negative symptoms. SST was not efficacious for improvement of negative symptoms in patients with TRS with predominantly negative symptoms, but caution is required to interpret these results due to the study's limitations. Abstract: We conducted a randomized controlled trial to assess the effectiveness of social skills training (SST) in improving negative symptoms in patients with treatment-resistant schizophrenia with predominantly negative symptoms. Patients were randomized to receive SST ( n  = 29) or to a control group ( n  = 33), in a 20-week program with weekly group sessions. Patients were assessed at baseline, post-treatment (20 weeks) and 6-month follow-up with the Positive and Negative Syndrome Scale. There was no significant improvement in the negative symptoms in either group, at any timepoint. Caution is warranted to interpret the results due to small sample size.